2021
DOI: 10.1002/chem.202005456
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Triphenyltriazine Triesters and the Induction of the Columnar Mesophase by Fluorine Substitution

Abstract: Whereas their para homologs are not mesogenic, the disk-shaped triphenyltriazine meta-trialkylesters obtained via trimerization of 3-cyanobenzoic alkylester, which are configurationally more flexible, exhibit a monotropic nematic mesophase. Introduction of fluorine atoms into the alkyl chains or into the phenyl moieties leads to the appearance of an enantiotropic columnar mesophase. If fluorine is introduced both in the chains and in the phenyl moieties, only a monotropic mesophase remains. Fluorination of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…10 Unfortunately, reports of discotic nematic phases remain relatively uncommon, and few molecular motifs have been identified that reliably give rise to these phases. 11–18…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Unfortunately, reports of discotic nematic phases remain relatively uncommon, and few molecular motifs have been identified that reliably give rise to these phases. 11–18…”
mentioning
confidence: 99%
“…10 Unfortunately, reports of discotic nematic phases remain relatively uncommon, and few molecular motifs have been identified that reliably give rise to these phases. [11][12][13][14][15][16][17][18] This study aims to develop new methods to promote nematic phases from simple discotic architectures. In the course of studying the liquid crystalline properties of dibenzo[a,c]phenazine (DBP) discotic mesogens, [19][20][21] we found that select derivatives, such as the carboxylic acid/pyridine complex A(10)-Pyr (10), form both columnar rectangular (Col r ) and nematic phases at elevated temperatures.…”
mentioning
confidence: 99%
“…We have earlier reported that methyl 3‐cyanobenzoate is trimerized in triflic acid at room temperature without substantial hydrolysis and degradation to non‐mesogenic 4 , whereas 3 itself and its longer‐chain homologs are better obtained by saponification of the methyl homolog 4 followed by appropriate re‐esterification than by the hydrolysis‐plagued trimerization of the appropriate alkyl 3‐cyanobenzoate [18] . We also noted previously that degradation upon attempted trimerization in triflic acid is a problem with 3‐cyanobenzoic acid, but not with 3‐cyanophenylacetic acid [17] .…”
Section: Resultsmentioning
confidence: 99%
“…CrÀ Col hex Col hex À Col hex Col hex -Iso Cr-Iso T g d col d disk 5 Et 224 [26] > 375 5 Pr 150 [13] > 375 81 Col 20.8 -5 Bu 108 [11] > 375 19 Col 23.5 3.3 7 Et 153 [12] 325 [26] 7 Pr 179 [1.9] 223 [3.0] 232 [37] 22.2 3.7 7 Bu 149 [1.0] 205 [34] 39 Col 22.5 3.7 7 Hex 123 [22] 27 Iso Chemistry-A European Journal diffraction pattern in the small angle region, but without loss of the ( 11) and ( 21) peaks.…”
Section: Crà Crmentioning
confidence: 99%
“…We recently reported that ester-substituted triphenyltriazines, i. e. tris(3-alkoxycarbonylphenyl)-s-triazines 1, (Scheme 3) can be obtained swiftly from methyl 3-cyanobenzoate in analogy to the acid-induced trimerization of benzonitrile, [10] and predominantly show nematic liquid crystal behavior. [11] Core-or chain-fluorination leads to columnar mesophases with only weak tendency to crystallize at room temperature, due to the rotational flexibility at the triazine-benzene single bond that allows for two in-plane configurations of each meta-attached ester group with respect to this bond. The limited conjugation between the three outer benzene units via meta-linkages through the central triazine cycle ensures that a large band gap is preserved, allowing for the embedding of blue emitters, as is desired eg.…”
Section: Introductionmentioning
confidence: 99%